Democracy: A Determinant Factor in Reducing Inflation - Fenira, Mohamed (International Journal of Economics and Financial Issues, 2014)
The economic literature has often explained the causes of macroeconomic instability by purely economic arguments. Monetary and fiscal policies have been considered as the exclusive tools for ensuring macroeconomic stability and reducing inflation. The purpose of this paper is to extend the range of explanatory factors in explaining macroeconomic pathologies and to demonstrate that democracy is an important instrument in reducing inflation. The paper firstly provides a critical analysis to the median voter theory, which claims the existence of a positive relationship between democracy and inflation, by relating the Tunisian case study and then presents a literature review that sustains our point of view. The paper finally develops an empirical study that measures the impact of democracy on inflation under a heterogeneous sample of countries and a sample consisting only of developing countries, for the period 1996-2012. The estimation results show that democracy is statistically significant in reducing inflation in both samples. Keywords: Democracy; Median voter theory; Kaufmann, Kraay and Mastruzzi (2012) democracy index; inflation; macroeconomic stabilization. JEL Classifications: E31; E61; E63